Jinx's fire - Blackwood, Sage
"Jinx travels throughout the Urwald to unite its people and creatures against encroaching threats"...
Sequel to: Jinx's magic
Keywords: JUVENILE FICTION / Science Fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Legends, Myths, Fables / General; Magic; Wizards; Orphans; Forests and forestry; Fantasy; Jugendbuch